Functional analysis of the putative ribosome biogenesis factor MoRei1 in Magnaporthe oryzae - TANG Shuai; XU Zhe; LÜ Wuyun; TONG Qi; XIAO Yu; WANG Zhengyi (浙江大学学报. 农业与生命科学版)
To further explore the biological roles of MoRei1 in the rice blast fungus Magnaporthe oryzae, we carried out MoREI1 gene deletion, phenotypic analysis of ΔMorei1 mutants, gene complementation and identification of its interaction proteins. The results showed that the ΔMorei1 mutants were defective in sexual reproduction, appressorium formation and pathogenicity. Deletion of MoREI1 led to significant increase of sensitivity to cell wall damaging and oxidative stress agents, and delay of glycogen mobilization and degradation during appressorium development. Moreover, the MoREI1 gene could partially complement the defects of Saccharomyces cerevisiae Δrei1 mutants, indicating that MoRei1 is a functional homolog of yeast Rei1, and may share a similar role in ribosome biogenesis. MoRei1 physically interacts with MoAlb1, a predicted nuclear export factor. Interestingly, deletion of MoREI1 resulted in the impairment of nuclear localization of MoAlb1. These results lay a foundation to clarify the roles of MoRei1 in fungal morphogenesis and pathogenicity in M. oryzae.